Macromolecular sensing at the liquid-liquid interface - Herzog, G.; Flynn, S.; Arrigan, Damien (IOP, 2011)
We report here the electrochemical sensing of macromolecules, such as polyLysine dendrimers, at the polarised liquid | liquid interface. Electrochemistry at the liquid | liquid interface is a powerful analytical technique which allows the detection of non-redox active molecules via ion transfer reactions at a polarised water – oil interface. We demonstrate here that different parameters of the polyLysine dendrimers (charge number, molecular weight) have a strong influence on the sensitivity and limit of detection of these macromolecules. This work will help to the development of sensors based on charge transfer at the liquid | liquid interface.